Delay-Prioritized Scheduling (DPS) for Real Time Traffic in 3GPP LTE System - Sandrasegaran, Kumbesan; Mohd. Ramli, Huda Adibah; Basukala, Riyaj (IEEE, 2010)
Given that the co-existence of multimedia applications will be a norm in the future wireless systems, their quality of service (QoS) requirements need to be guaranteed. This has imposed new challenges in the design of packet scheduling algorithms in these systems. To address those challenges, a new packet scheduling algorithm for real time (RT) traffic in downlink third generation partnership project long term evolution (3GPP LTE) system is proposed in this paper. The proposed algorithm utilizes each user’s packet delay information and its instantaneous downlink channel conditions when making scheduling decisions. Simulation results show that the proposed algorithm outperforms opportunistic scheduling and maximum-largest weighted delay first algorithms by maximizing system throughput and satisfying the QoS requirements of the RT traffic.